2015
DOI: 10.3855/jidc.6670
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Chikungunya virus in the north Caribbean area of Colombia: clinical presentation and phylogenetic analysis

Abstract: Introduction: The Caribbean area of Colombia has been severely affected by a Chikungunya virus (CHIKV) outbreak since 2014. Methodology: The study was carried out on 100 patients during a fever outbreak from August to September 2014 in two small rural villages in the northern Caribbean area of Colombia. The molecular assays performed by reverse transcription polymerase chain reaction (RT-PCR) on acute patient sera were collected within one to five days of the appearance of symptoms. Sequence analyses were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 22 publications
6
38
1
3
Order By: Relevance
“…In Trinidad and Tobago, 83.3% of confirmed patients complained of joint pain, while arthralgia was reported in 96% of patients in Colombia [19, 34]. In our study, although arthritis was not reported by any physician, there was relatively little arthralgia associated with CHIKV infection, with only 20.0% of patients reporting joint pain.…”
Section: Discussioncontrasting
confidence: 47%
“…In Trinidad and Tobago, 83.3% of confirmed patients complained of joint pain, while arthralgia was reported in 96% of patients in Colombia [19, 34]. In our study, although arthritis was not reported by any physician, there was relatively little arthralgia associated with CHIKV infection, with only 20.0% of patients reporting joint pain.…”
Section: Discussioncontrasting
confidence: 47%
“…Most patients showed the same common features described in previous CHIKF outbreaks including the Colombian epidemic. 39 Of the 32 patients, 26 experienced fever (81%), 23 rash (72%), 21 arthralgia (65%), 19 myalgia (59%), and 11 headache (34%). These results were similar to others previously described in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…British Virgin Islands (Lanciotti and Valadere 2014), Guadeloupe, Martinique (Stapleford et al 2016) and Trinidad (Sahadeo et al 2015)] and from the American mainland [i.e. Colombia (Mattar et al 2015), Panama (Diaz et al 2015), Mexico (Diaz-Quinonez et al 2015) and Brazil (Nunes et al 2015)] also confirmed circulation of the Asian lineage. However, in Brazil, concurrent with the Asian genotype CHIKV circulation, there was an outbreak in the east-central region of Feira de Santana that was caused by a newly introduced ECSA strain (Nunes et al 2015).…”
Section: Introductionmentioning
confidence: 82%